Development of Biology Learning Media Assisted by Construct2 to Improve Critical Thinking Skills - M. Noris; Sulistyo Saputro; Muzzazinah Muzzazinah; Ayu Rahayu (Jurnal Penelitian Pendidikan IPA, 2023)
The construct2 software is an HTML5 based Game Builder Tool. Construct2 can be used in the development of biology learning media assisted by construct2 or HTML5 to improve critical thinking skills. This type of research is research and development (Research and Development) which is accommodated from Sugiyono (2008) which was developed according to the conditions and situations. The research data instruments consist of assessment instruments by validators (material, language, and media), and media-based questionnaires based on teacher and student responses. The research data is in the form of media data validation from a team of experts, the results of the virtual laboratory media feasibility test, and the results of the learning media effectiveness test. The research population consisted of 5 SMA 1 BELO classes consisting of IPA 1, IPA 2, IPA 3, IPA 4 with a total of 130 students. The research subjects consisted of 67 students from Senior High School Negeri 1 Belo, West Nusa Tenggara, Indonesia. The result of the research is an application-based virtual laboratory application that can be programmed using Construct2 or HTML5 software. The results of the validity test according to experts ranged from 97%, while the exact location was 87%. The implications of this research are expected to be able to contribute to researchers, practitioners, to be able to optimize construction in making 3-dimensional virtual laboratory media